AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN KEUANGAN MASJID DI KOTA BANDA ACEH - khairaturrahmi, khairaturrahmi; Ibrahim, Ridwan (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This study has purpose to describe how accountability and transparancy in financial management at the mosques in Banda Aceh . This study is descriptive qualitative study. Data is collected by interview to mosques management in Banda Aceh . The primary data collected by interview is used in this study. The results of this study indicate that generally, the Mosques in Banda Aceh were not fully implemented transprancy and accountability in its financial management